Cost-effectiveness of interventions to reduce dietary salt intake. - Cobiac, L; Vos, T; Veerman, J (2010)
OBJECTIVE: To evaluate population health benefits and cost-effectiveness of interventions for reducing salt in the diet. DESIGN: Proportional multistate life-table modelling of cardiovascular disease and health sector cost outcomes over the lifetime of the Australian population in 2003. INTERVENTIONS: The current Australian programme of incentives to the food industry for moderate reduction of salt in processed foods; a government mandate of moderate salt limits in processed foods; dietary advice for everyone at increased risk of cardiovascular disease and dietary advice for those at high risk. MAIN OUTCOME MEASURES: Costs measured in Australian dollars for the year 2003. Health outcomes measured in disability-adjusted life years (DALY) averted over the lifetime. RESULTS: Mandatory and voluntary reductions in the salt content of processed food are cost-saving interventions under all modelled scenarios of discounting, costing and cardiovascular disease risk reversal (dominant cost-effectiveness ratios). Dietary advice targeting individuals is not cost-effective under any of the modelled scenarios, even if directed at those with highest blood pressure risk only (best case median cost-effectiveness A$100 000/DALY; 95% uncertainty interval A$64 000/DALY to A$180 000/DALY). Although the current programme that relies on voluntary action by the food industry is cost-effective, the population health benefits could be 20 times greater with government legislation on moderate salt limits in processed foods. CONCLUSIONS: Programmes to encourage the food industry to reduce salt in processed foods are highly recommended for improving population health and reducing health sector spending in the long term, but regulatory action from government may be needed to achieve the potential of significant improvements in population health.